Assessing the values and impacts of invasive alien plants on the livelihoods of rural land-users on the Agulhas Plain, South Africa - De la Fontaine, Samantha (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.